2023
DOI: 10.1101/2023.05.09.540053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SKP2 knockout in Rb1/p53 deficient mouse models of osteosarcoma induces immune infiltration and drives a transcriptional program with a favorable prognosis

Abstract: Purpose: Osteosarcoma (OS) is an aggressive bone malignancy with a poor prognosis. One putative proto-oncogene in OS is SKP2, encoding a substrate recognition factor of the SCF E3 ubiquitin ligase. We previously demonstrated that SKP2 knockout in murine OS improved survival and delayed tumorigenesis. Here we aim to define the SKP2 drives transcriptional program and its clinical implication in OS. Experimental Design: We performed RNA-sequencing (RNA-seq) on tumors from a transgenic OS mouse model with conditio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…They primarily restrict tumor growth by inducing G1 phase cell cycle arrest, a mechanism that may involve downregulation of SKP2 79 . Additionally, SKP2 knockdown has been found to significantly increase the expression of immunoinfiltration-related genes in osteosarcoma (OS) mouse models, suggesting that SKP2 may mediate rejection in the tumor microenvironment 80 .…”
Section: Discussionmentioning
confidence: 99%
“…They primarily restrict tumor growth by inducing G1 phase cell cycle arrest, a mechanism that may involve downregulation of SKP2 79 . Additionally, SKP2 knockdown has been found to significantly increase the expression of immunoinfiltration-related genes in osteosarcoma (OS) mouse models, suggesting that SKP2 may mediate rejection in the tumor microenvironment 80 .…”
Section: Discussionmentioning
confidence: 99%
“…Their discovery suggests potential novel targets for therapeutic intervention, thereby expanding our understanding of OS’s complex molecular pathways [ 94 ]. In a pivotal study, Ferrena et al utilized mouse models deficient in Retinoblastoma 1 (Rb1) and Tumor Protein p53—two key genes in OS—to examine the effects of SKP2 knockout [ 95 ]. Their results revealed that SKP2 deficiency induced significant immune infiltration within the tumor microenvironment, suggesting a potential immune response against OS [ 95 ].…”
Section: Advance In Os Cells and Modelsmentioning
confidence: 99%
“…In a pivotal study, Ferrena et al utilized mouse models deficient in Retinoblastoma 1 (Rb1) and Tumor Protein p53—two key genes in OS—to examine the effects of SKP2 knockout [ 95 ]. Their results revealed that SKP2 deficiency induced significant immune infiltration within the tumor microenvironment, suggesting a potential immune response against OS [ 95 ]. Further, the SKP2 knockout triggered a transcriptional program associated with a favorable prognosis [ 95 ].…”
Section: Advance In Os Cells and Modelsmentioning
confidence: 99%
See 2 more Smart Citations